2022
DOI: 10.1071/sb21030_co
|View full text |Cite
|
Sign up to set email alerts
|

<i>Corrigendum to</i>: Morphological and molecular evidence refute a broad circumscription for <i>Pultenaea glabra</i> (Fabaceae: Mirbelieae), with implications for taxonomy, biogeography, and conservation

Abstract: The publisher regrets to inform readers that, owing to the incorrect pagination of an earlier paper, the paper by Renner et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…praecipua (previously P. sp. Genowlan Point) was one of eight new Pultenaea taxa recently described in the Blue Mountains (Renner et al 2022). It was found to be severely affected by P. cinnamomi in a glasshouse study (Wan et al 2019); none of the other seven new taxa has been tested for susceptibility to P. cinnamomi.…”
Section: Dillwynia Tenuifoliamentioning
confidence: 99%
“…praecipua (previously P. sp. Genowlan Point) was one of eight new Pultenaea taxa recently described in the Blue Mountains (Renner et al 2022). It was found to be severely affected by P. cinnamomi in a glasshouse study (Wan et al 2019); none of the other seven new taxa has been tested for susceptibility to P. cinnamomi.…”
Section: Dillwynia Tenuifoliamentioning
confidence: 99%
“…2016; Rossetto et al . 2021), as well as testing the identity of questionable populations or unknown samples (Renner et al . 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Pultenaea Sm. as currently circumscribed is a relatively large genus of over 150 species (Barrett et al 2021;Renner et al 2022) with most species found in south-eastern Australia. Orthia et al (2005) suggested that generic circumscriptions in tribe Mirbelieae may need major revision.…”
Section: Introductionmentioning
confidence: 99%
“…As P. flexilis is a sister lineage to the P. glabra complex, the new species described here is also likely related to the broader P. glabra complex. However, that group has recently been revised and the taxon we describe here is morphologically distinct (Renner et al 2022).…”
Section: Introductionmentioning
confidence: 99%